Young adults' dynamic relationships with their families in early psychosis: Identifying relational strengths and supporting relational agency. (27th March 2021) - Boden‐Stuart, Zoë V. R.; Larkin, Michael; Harrop, Chris
Abstract : Objectives: Most existing research on the family context of psychosis focuses on the 'burden' of caring for people experiencing psychosis. This research is the first to ask young people experiencing early psychosis to 'map' and describe their experiences and understandings of their family relationships, and how they have related to their psychosis and recovery. Design: The research took an inductive, multimodal hermeneutic–phenomenological approach (Boden, Larkin & Iyer, 2019, Qual. Res. Psychology, 16, 218‐236; Boden & Larkin, 2020, A handbook of visual methods in psychology, 358‐375). Method: Ten young adults (18–23), under the care of early intervention in psychosis services in the UK, participated in an innovative relational mapping interview (Boden, Larkin & Iyer, 2018), which invited participants to draw a subjective 'map' of their important relationships. This visual methodology enables subtle, complex, ambivalent, and ambiguous aspects of the participants' experiences to be explored. Results: Findings explore the participants' accounts of how they love, protect, and care for their families; how they wrestle with family ties as they mature; and their feelings about talking about their mental health with loved ones, which was typically very difficult. Conclusions: This paper advances understanding of recovery in psychosis through consideration of the importance of reciprocity, and the identification and nurturance of relational strengths. The capacity of a young person to withdraw or hold back when trying to protect others is understood as an example of relational agency. The possibility for extending strengths‐based approaches and family work within the context of early intervention in psychosis services is discussed. Practitioner points: Young adults experiencing early psychosis may benefit from support to identify their relational strengths and the opportunities they have for reciprocity within their family structures, where appropriate. Relational motivations may be important for a range of behaviours, including social withdrawal and non‐communication. Services may benefit from exploring the young person's relational context and subjective meaning‐making in regard to these actions. Young adults experiencing early psychosis may benefit from opportunities to make sense of their family dynamics and how this impacts on their recovery. Attachment‐based and relationally oriented interventions that increase trust and openness, and reduce feelings of burdensomeness are likely to support family functioning as well as individual recovery.